International Biomass Trade and Sustainable Development: An Overview - Catalin Chiriac; Nicoleta Rusu (CES Working Papers, 2011)
It is crystal clear that the neoclassical economical theory, despite being probably the best growth model ever invented by man, tickled a cost of environmental degradation which can threaten our wealth and even our existence. For this reason, the concept of sustainable development (SD) is so empathic, being considered probably the best theoretical alternative invented by man to standard growth, because of its vision of a better world, where economics, society and environment are intimately linked. Thus, all human activities have to adapt to this new paradigm, in order to achieve its goals. From the economical perspective, production, consumption and trade must incorporate a kind of sustainable type of activity. In the recent years, growing demands in energy use and the increase of oil and coal prices, have led to the usage of new energy sources such as biomass, water, solar, wind and geothermal energy. This is why we propose in this paper to present an overview of international trade in biomass reported to the philosophy of SD. In short, we want to give an answer at two questions: how much is biomass trade sustainable and what risks may arise if the main source of energy used today, based on fossil fuels, will be totally substitute by biomass? To be sustainable, biomass, must meet certain criteria, such as: to possess a high capacity for regeneration, in a relatively short time; to offer a better efficiency compared with the traditional fossil fuel sources; to be less or non-polluting, to be used in solid, liquid and gaseous form; to have a broad applicability in production and consumption; to have a competitive level in terms of costs and prices for transport or storage, in both stages, as a raw material or as a finished product; to be a good substitute of traditional fuels (gasoline or diesel), without the necessity for structural changes of the of the engine. The article will conclude that the uprising trend of the EU biomass trade and consumption will continue, because of grown concerns of the EU Member States regarding the effects that greenhouse gas emissions have over the environment and over the quality of life standard, despite the critics which states that biomass production may have negative environmental effects, leading to massive deforestation and destruction of soil, water sources and natural habitat.
Keywords: Q01; F18; 330; sustainable development; international trade; environmental impact; biomass; biofuels Romania